2012
DOI: 10.1016/j.jcrs.2012.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based guidelines for cataract surgery: Guidelines based on data in the European Registry of Quality Outcomes for Cataract and Refractive Surgery database

Abstract: In March 2008, the European Registry of Quality Outcomes for Cataract and Refractive Surgery (EUREQUO) commenced. This 3-year project was cofunded by the European Union (EU) and the European Society of Cataract & Refractive Surgeons (ESCRS). The ESCRS became the lead partner in the project with 11 national societies as associated partners. The aims of the project were to improve treatment and standards of care for cataract and refractive surgery and to develop evidence-based guidelines for cataract and refract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
124
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(139 citation statements)
references
References 25 publications
10
124
0
5
Order By: Relevance
“…Another benchmark for comparison was the results of the European Registry of Quality Outcomes for Cataract and Refractive Surgery (EUREQUO) database. A benchmark of at least 87 % of surgeries having a refractive outcome of a spherical equivalent within ±1D of the targeted refraction and a mean biometric prediction error of 0.6D was recommended in this study [11]. Their figure of 87 % was nearly matched by our figures, and the mean biometric prediction error of 0.53D in our data also fell within these benchmarks.…”
Section: Prediction Of Refractive Outcomessupporting
confidence: 78%
“…Another benchmark for comparison was the results of the European Registry of Quality Outcomes for Cataract and Refractive Surgery (EUREQUO) database. A benchmark of at least 87 % of surgeries having a refractive outcome of a spherical equivalent within ±1D of the targeted refraction and a mean biometric prediction error of 0.6D was recommended in this study [11]. Their figure of 87 % was nearly matched by our figures, and the mean biometric prediction error of 0.53D in our data also fell within these benchmarks.…”
Section: Prediction Of Refractive Outcomessupporting
confidence: 78%
“…This trend is consistent with the rate of 1.1% reported by Zaidi et al 12 at the Western Eye Hospital in London in 2007. A recent large-scale European study including 11 national societies reported a total capsule complication rate of 1.2% 14. It is possible that the lower rate of PCR in this study is due to the difference in the period at which the data was collected.…”
Section: Discussionmentioning
confidence: 73%
“…The European Registry of Quality Outcomes for Cataract and Refractive Surgery has one of the largest and most current databases collected to date regarding the overall outcomes of cataract surgery (more than 500 000 cases treated between January 2009 and August 2011). 12 In eyes for which postoperative refractive data were available, 91.5% of results were within G1.00 D of the target refraction. Behndig et al 13 report similar results for a Swedish outcomes registry containing more than 15 000 eyes; 71% of eyes were within G0.50 D of the target refraction and 93% were within 1.00 D. Gale et al 14 analyzed a United Kingdom outcomes database over 3 audit periods and found results within G0.50 D for between 49% and 60% of eyes and results within G1.00 D for between 80% and 87% of eyes.…”
Section: Discussionmentioning
confidence: 93%